Effects of khat ethanol extract, cathinone and cathine on cytochrome P450 activities in vitro, molecular docking CYP-cathinone and CYP-cathine interactions and in vivo effects on Caenorhabditis elegans - Lim, Sharoen Yu Ming (2024)
Khat (Catha edulis Forsk), a natural amphetamine-like psychostimulant plant, and its major active compounds cathinone and cathine are consumed by many not only for cultural practice but also for its appetite suppressing effects and often co-abused with alcohols and polydrugs. Concurrent intake of herbs and clinical drugs may lead to herb-drug interactions (HDIs) and adverse drug reactions (ADRs). Ensuing the previous in vitro findings that khat ethanol extract (KEE) inhibited major human drug metabolizing cytochrome P450 (CYP) including CYP2C9, CYP2D6 and CYP3A4, this study showed that (i) KEE inhibited human CYP2A6, CYP2B6, CYP2C8, CYP2C19, CYP2E1, CYP2J2, CYP3A5, (ii) cathinone inhibited CYP1A2, CYP2A6 and CYP3A5, and (iii) cathine inhibited CYP2A6 and CYP3A4. The in silico molecular docking studies demonstrated binding modes and key interactions including hydrogen bonding, hydrophobic interactions and π-π stacking of cathinone and cathine relative to haem group in the active sites of CYP1A2, CYP2A6, CYP3A5 and CYP2A6, CYP3A4 respectively. In vivo studies using Caenorhabditis elegans (C. elegans) demonstrated that KEE, cathinone and cathine treatment led to visible reduction in C. elegans feeding and reproduction rate, however interestingly, extended lifespan of the nematodes. Quantitative RT-PCR results showed that the C. elegans cyp-14A3, cyp-34A9 and cyp-35A2 which has the closest homolog to human CYP1 and CYP2 family, were insignificant but upregulated upon exposures to KEE, cathinone, cathine and sibutramine as compared to control treatment. Khat-drug, cathinone-drug or cathine-drug interactions may occur with potentially clinically-significant implications on users who are taking medications that are metabolized by all the 11 major human drug metabolising CYPs. Our in vivo findings could answer part of the hunt for cyp genes regulation upon exposures to khat and its active compounds. Further ventures may have the power to elucidate other gene targets within the pathway and possibly a novel and successful medical regime to herb-drug interactions and cyps gene-related diseases.